CovInter: interaction data between coronavirus RNAs and host proteins. Issue Volume 51:Issue D1(2023) (6th October 2022) - Amahong, Kuerbannisha; Zhang, Wei; Zhou, Ying; Zhang, Song; Yin, Jiayi; Li, Fengcheng; Xu, Hongquan; Yan, Tianci; Yue, Zixuan; Liu, Yuhong; Hou, Tingjun; Qiu, Yunqing; et al.
Abstract: Coronavirus has brought about three massive outbreaks in the past two decades. Each step of its life cycle invariably depends on the interactions among virus and host molecules. The interaction between virus RNA and host protein (IVRHP) is unique compared to other virus–host molecular interactions and represents not only an attempt by viruses to promote their translation/replication, but also the host's endeavor to combat viral pathogenicity. In other words, there is an urgent need to develop a database for providing such IVRHP data. In this study, a new database was therefore constructed to describe the interactions between coronavirus RNAs and host proteins (CovInter). This database is unique in (a ) unambiguously characterizing the interactions between virus RNA and host protein, (b ) comprehensively providing experimentally validated biological function for hundreds of host proteins key in viral infection and (c ) systematically quantifying the differential expression patterns (before and after infection) of these key proteins. Given the devastating and persistent threat of coronaviruses, CovInter is highly expected to fill the gap in the whole process of the 'molecular arms race' between viruses and their hosts, which will then aid in the discovery of new antiviral therapies. It's now free and publicly accessible at: https://idrblab.org/covinter/ Graphical Abstract: